Great people of the Bible - Reader's Digest Association; Questar, Inc. ([United States] : Readers Digest Association ; Chicago, IL : Distributed by Questar, 2003)
Abraham, Sarah, Isaac, Jacob, Joseph, and Paul. Their faith, words and deeds marked the path that Christianity would follow generation after generation. These accounts have been filmed on locations featuring ancient cities and sacred sites.
DVD, region 1, full screen presentation; Dolby Digital stereo, Dolby Digital 5.1 surround.
Title from container.
MPAA rating: Not rated.
Keywords: Abraham -- (Biblical patriarch); Sarah -- (Biblical matriarch); Isaac -- (Biblical patriarch); Jacob -- (Biblical patriarch); Joseph -- (Son of Jacob); Paul, -- the Apostle, Saint; Bible -- Biography; Religious films